2016
DOI: 10.1371/journal.pone.0159134
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Substance Use among Forced Migrants: A Global Systematic Review

Abstract: IntroductionForced migration is occurring at unprecedented levels. Forced migrants may be at risk for substance use for reasons including coping with traumatic experiences, co-morbid mental health disorders, acculturation challenges and social and economic inequality. This paper aimed to systematically review the literature examining substance use among forced migrants, and identify priority areas for intervention and future research.MethodsSeven medical, allied health and social science databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(158 citation statements)
references
References 139 publications
4
137
3
4
Order By: Relevance
“…The reported prevalence of drug and substance misuse varies greatly among forced migrants, depending on the study population, including origin country and cultural norms 32. In the current study, drug and alcohol use was reported only among males and the overall frequency was low compared with other non-refugee adolescent groups, including those who have experienced abuse/neglect 15.…”
Section: Discussionmentioning
confidence: 51%
“…The reported prevalence of drug and substance misuse varies greatly among forced migrants, depending on the study population, including origin country and cultural norms 32. In the current study, drug and alcohol use was reported only among males and the overall frequency was low compared with other non-refugee adolescent groups, including those who have experienced abuse/neglect 15.…”
Section: Discussionmentioning
confidence: 51%
“…() found that the prevalence rates for PTSD and depression were 30.6% and 30.8%, respectively. In addition to PTSD, depression, and anxiety, refugees also experience issues such as dissociation (Carlson & Rosser‐Hogan, ), somatic complaints (van Ommeren et al., ), and elevated rates of substance use (Horyniak, Melo, Farrell, Ojeda, & Strathdee, ).…”
Section: Factors Affecting Refugees’ Mental Healthmentioning
confidence: 99%
“…This mode of migration is associated with highly constraining risk environments for injection-related harms, given a variety of stressors—including fear of deportation, housing instability, compromised basic human rights, and forced return migration—associated with injection-related risks (Apostolopoulos et al, 2006; Hacker et al, 2011). Reviews of substance use and migrant health literature have concluded that forced migrants, including deported migrants, are particularly vulnerable to initiating problematic substance use (Horyniak et al, 2016a), as forced migration disrupts social networks, which in turn heightens the risk of injection initiation as a coping mechanism (Higgs et al, 2008; Ojeda et al, 2011; Wagner et al, 2011). …”
Section: Migration Classes and Injection Initiationmentioning
confidence: 99%
“…Migrant populations have also been shown to be at risk of initiating injection drug use (IDU) (Folch et al, 2016; Horyniak, Melo, Farrell, Ojeda,& Strathdee, 2016a; Ojeda et al, 2011), especially those populations whose migration pathways traverse drug trafficking regions (Beyrer et al, 2000; Rachlis et al, 2007). Relatedly, dual epidemics of IDU and blood-borne disease have been observed across international borders and drug trafficking routes globally (Beyrer et al, 2000; Rachlis et al, 2007; Strathdee, Magis-Rodriguez, Mays, Jimenez, & Patterson, 2012).…”
Section: Introductionmentioning
confidence: 99%